Autorytet wykładowcy kształcenia dorosłych i jego kontekst pedagogiczny - Vališová, Alena; Čapek Adamec, Martin (Studia Edukacyjne, 2025)
Authority remains one of the most contested yet indispensable concepts in contemporary adult education. This paper explores the authority of the adult education lecturer from philosophical, sociological, and pedagogical perspectives. It highlights the interdependence of authority, freedom, and responsibility in adult learning environments. Building upon previous theoretical work, the study integrates an empirical component based on interviews with Czech adult education lecturers, identifying major dimensions of authority in practice. The discussion situates these findings within current debates on lifelong learning, democratic education, and professional ethics.